Estratégias e tecnologias da informação e comunicação para a educação corporativa visando ao desenvolvimento de lideranças em empresas multisite - Moscardini, Ticiana Nunes (Universidade do Vale do Rio dos Sinos, 2013)
In the business world, answers for changes must be increasingly agile, mainly speaking of information based society. Therefore, the capability becomes a top trend in the corporate world where training and development (T&D) actions used to be promoted. Learning is currently in a transformation process and, in this context; we have Corporate Education (CE), which can be defined as a set of continuous educational strategies grounded on future goals and organizational culture, aiming at developing critical competencies for business, involving internal and external company parties. As an actionwithin CE, leadership development, in a social context, is attached to organization needs, and seeks for a structured way to elaborate programs for continuous development. In order to achieve leadership development, different strategies, modalities and Information Technology and Communication (ITC) can be used. This research is motivated by this scenario, since there are few academic studies about CE and leadership development in multisite organization in Porto Alegre metropolitan area. This investigation is based on an exploratory qualitative research, through interviews in 12 big companies, with 24 people by means of a semi-structured script. An analysis protocol was created based on categories identified in the bibliography review using Nvivo software. The results point out that the majority of the companies still do not have adopted Corporate Education completely. The most popular teaching and learning strategies are: expositive classes, debates, coaching and workshops; mainly inplace and ITC are barely applied, such technologies are also known as Virtual Learning Environments (VLE) and Web 2.0 tools. Considering that the researched companies are multisite, the main challenge in leadership development is the organizational culture learning and dissemination. With the leadership development programs results, the interviewees cited: knowledge dissemination, collective vision (common objectives) and financial results, but it is evident that there are still a big issue in most of the researched companies in terms of evaluation, in a systematic way, CE and leadership development results.
Keywords: Educação corporativa; Desenvolvimento de lideranças; Tecnologia da informação e comunicação; TIC; Empresas multisite; Corporate education; Leadership development; Information technology and communication; ITC; Multisite companies; ACCNPQ::Ciências Sociais Aplicadas::Administração